Socio-economic Inequality of Outpatient and Inpatient Healthcare Services: A Crosssectional Study in Iran - Parisa Naseri; Bahman Ahadinejad; Mohammad Amerzadeh; Fariba Hashemi; Sima Rafiei (Shiraz University of Medical Sciences, 2024)
Background: Ensuring equal utilization of health services has always been a priority in health systems globally. Iran implemented reforms such as the Health Transformation Plan (HTP), in which one objective was to reduce inequity in access to inpatient and outpatient services. These studies aimed to measure inequality in health services utilization in Qazvin, Iran, and clarify inpatient and outpatient utilization patterns among socioeconomic subgroups of the population.Methods: This cross-sectional study recruited 442 households living in Qazvin, Iran, in 2019. We collected data using a tool that included demographic characteristics, socioeconomic status, and health services utilization. We applied the concentration index to measure inequality and performed data analysis using STATA 15.Results: Based on our estimates, the utilization rates of outpatient and inpatient services in the study sample were 0.89±1.39 and 0.45±0.94, respectively. There was no statistically significant difference in the use of outpatient healthcare services in terms of gender and insurance coverage of the households, while literacy, age, and health condition had statistically significant effects on inpatient healthcare utilization (P<0.05). Furthermore, the marginal effects of age and literacy on the utilization of outpatient services were statistically significant (P<0.05), so that literacy and aging increased the outpatient HSU. Except for age, the marginal effects of other characteristics on the utilization of inpatient services were statistically significant (P<0.05).Conclusion: Our findings indicated that inequality in healthcare utilization reduced over time, showing that in addition to reducing inequality in HSU, population groups with lower socio-economic status have benefited more from both inpatient and outpatient services.